Update on Hand Osteoarthritis: A Neglected Problem - Daniella, Dian; -, Marianto (Cermin Dunia Kedokteran, 2020)
Osteoarthritis (OA) is the most common rheumatologic disease and one of the leading causes of disability worldwide. Hand OA is the most common OA types after knee and hip OA. Risk factors include age, obesity, and family history. Abnormal mechanical loads, sex hormones, and inflammatory changes play role in pathogenesis of hand OA. Diagnosis is primarily based on clinical examination according to ACR guidelines. Plain radiography may support the diagnosis. ACR 2019 recommends comprehensive individualized treatment which include single or combination of physical, psychosocial, and/or pharmacological intervention. Topical NSAIDs are conditionally recommended. For initial oral medication, oral NSAIDs are strongly recommended and preferable to other medications. Exercise is also strongly recommended. Hand orthoses are highly recommended for patients with first CMCJ OA and conditionally recommended for patients with OA in other joints of the hand.Osteoartritis (OA) adalah penyakit reumatologis paling umum dan salah satu penyebab utama kecacatan di seluruh dunia. Osteoartritis tangan adalah jenis OA yang paling umum setelah OA lutut dan pinggul. Faktor risiko penyakit ini adalah usia, obesitas, dan riwayat keluarga. Beban mekanis abnormal, hormon seks, dan reaksi inflamasi juga berperan pada patogenesis OA tangan. Diagnosis OA tangan dapat ditegakkan klinis sesuai pedoman ACR. Pemeriksaan radiologis dapat membantu diagnosis. Pedoman ACR 2019 merekomendasikan tatalaksana komprehensif tunggal atau gabungan dari intervensi fisik, psikososial, dan/atau farmakologis sesuai kebutuhan pasien. OAINS topikal direkomendasikan untuk OA tangan pada kondisi tertentu. Untuk pengobatan oral awal, OAINS oral direkomendasikan sebagai pilihan utama. Olahraga sangat direkomendasikan termasuk untuk OA tangan. Orthosis tangan sangat dianjurkan untuk pasien CMCJ OA awal dan direkomendasikan pada pasien OA persendian tangan lain dengan kondisi tertentu.Â